2011
DOI: 10.1371/journal.ppat.1002330
|View full text |Cite
|
Sign up to set email alerts
|

HacA-Independent Functions of the ER Stress Sensor IreA Synergize with the Canonical UPR to Influence Virulence Traits in Aspergillus fumigatus

Abstract: Endoplasmic reticulum (ER) stress is a condition in which the protein folding capacity of the ER becomes overwhelmed by an increased demand for secretion or by exposure to compounds that disrupt ER homeostasis. In yeast and other fungi, the accumulation of unfolded proteins is detected by the ER-transmembrane sensor IreA/Ire1, which responds by cleaving an intron from the downstream cytoplasmic mRNA HacA/Hac1, allowing for the translation of a transcription factor that coordinates a series of adaptive response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
188
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(212 citation statements)
references
References 63 publications
16
188
3
3
Order By: Relevance
“…An emerging body of evidence suggests that the secretory pathway of filamentous fungi is a point of vulnerability that could be accessible to therapeutic intervention (6,7). The genome of A. fumigatus, like those of many other environmental saprophytic fungi, is enriched for secreted hydrolytic enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An emerging body of evidence suggests that the secretory pathway of filamentous fungi is a point of vulnerability that could be accessible to therapeutic intervention (6,7). The genome of A. fumigatus, like those of many other environmental saprophytic fungi, is enriched for secreted hydrolytic enzymes.…”
mentioning
confidence: 99%
“…This is accomplished by remodeling gene expression to expand the protein-folding capacity of the ER in proportion to the accumulation of unfolded nascent proteins in the ER lumen. The A. fumigatus UPR is regulated by IreA (Ire1 in yeast and higher eukaryotes), a molecular sensor embedded in the ER membrane that is comprised of a lumenal sensing domain and a cytosolic effector domain (6). Studies in Saccharomyces cerevisiae have shown that unfolded proteins trigger oligomerization of this protein in the ER membrane, which activates the cytosolic domain and induces the expression of a bZIP transcription factor known as HacA in filamentous fungi (10).…”
mentioning
confidence: 99%
“…48 The expression levels of some ergosterol biosynthesis genes, including ERG2, ERG11, ERG24, and ERG3, decrease in both ireAΔ and hacAΔ mutants in A. fumigatus and subsequent ergosterol levels in both stains are reduced. In Cryptococcus, ire1Δ and hxl1Δ mutants also show significantly enhanced susceptibility to azole drugs, including fluconazole, ketoconazole, and itraconazole, although the mechanism appears to be different from that of A. fumigatus based on several observations.…”
Section: Potential For the Upr Pathway As A Novel Antifungal Therapeumentioning
confidence: 96%
“…Comprehensive gene expression analysis of the UPR pathways in Caenorhabditis elegans and A. fumigatus strongly support the divergent regulation of Ire1 and Hac1 orthologs. 47,48 Moreover, in metazoans, the endoribonuclease activity of Ire1 was directly involved in controlling the expression of a subset of genes encoding ER proteins by degrading mRNA to reduce the unfolded protein load in the ER lumen. 49,50 It was thus proposed that Ire1 selectively degrades groups of ER-bound mRNAs to relieve the burden of unfolded proteins in the ER lumen via the regulated Ire1-dependent decay (RIDD) pathway.…”
Section: Hxl1-independent Ire1 Functions In the Cryptococcus Upr Pathwaymentioning
confidence: 99%
See 1 more Smart Citation